Effects of 10 Hz Repetitive Transcranial Magnetic Stimulation of the Left Dorsolateral Prefrontal Cortex in Disorders of Consciousness - Xia, Xiaoyu; Bai, Yang; Zhou, Yangzhong; Yang, Yi; Xu, Ruxiang; Gao, Xiaorong; Li, Xiaoli; He, Jianghong (Frontiers in Neurology, 2017)
Background: While repetitive transcranial magnetic stimulation (rTMS) has been applied in treatment of patients with disorders of consciousness (DOC), a standardised stimulation protocol has not been proposed, and its therapeutic effects are inconsistently documented. Objectives: To assess the efficacy of rTMS in improving consciousness in patients with persistent minimally conscious state (MCS) or unresponsive wakefulness syndrome (UWS), previously known as vegetative state (VS). Method: A prospective single-blinded study, with selected subjects, was carried out. In total, 16 patients (5 MCS and 11 VS/UWS) with chronic DOC were included. All patients received active 10Hz rTMS at the left dorsolateral prefrontal cortex (DLPFC), at one session per day, for 20 consecutive days. A single daily session of stimulation consisted of 1,000 pulses (10 seconds of 10Hz trains, repeated 10 times with an inter-train interval of 60 seconds, 11 minutes and 40 seconds for total session). The main outcome measures were changes in the total score on the JFK Coma Recovery Scale-Revised (CRS-R) scale. Additional measures were the impressions of caregivers after the conclusion of the interventions, which were assessed using the Global Impression Improvement (CGI-I) scale. Results: The CRS-R scores were increased in all 5 MCS patients and 4 out of 11 VS/UWS patients, while a significant enhancement of CRS-R scores was observed compared to the baseline in all participants (p = 0.007). However, the improvement was more notable in MCS patients (p = 0.042) than their VS/UWS counterparts (p = 0.066). Based on the CGI-I scores, two patients improved considerably, two improved, six minimally improved, six experienced no change and none deteriorated. Good concordance was seen between the CGI-I result and the increases in CRS-R scores. Conclusion: Treatment of 10Hz multisession rTMS applied to the left DLPFC is promising for the rehabilitation of DOC patients, especially those in MCS. Further validation with a cohort of a larger sample size is required.